An evaluation of body size as related to weight of three West African breeds of cattle in Nigeria - Buvanendran, V.; Umoh, J.E.; Abubakar, B.Y. (Cambridge University Press, 1980)
Body measurements have been used to predict live weights of cattle, an important variable in determining market value of an animal. Animals of varying ages from White Fulani (Bunaji), Sokoto Gudali and the N'Dama breeds of cattle were evaluated to determine the relationships between weights and body measurements. Chest girth accounted for 86 to 96 percent of the variation in body weight in the three breeds. The linear regression coefficient of weight of chest girth in the N'Dama differed significantly from the other two breeds. Within each breed, the regression coefficient of young animals was lower than those of older groups. The variables that contributed most to improving the prediction of weights when added to chest girth were rump length and body length. Live weight estimates of indigenous breeds of cattle in Nigeria can be made with the same precision as with the European breeds of cattle using chest girth measurements. Such estimates should consider not only the breed type but also age and condition in order to improve the accuracy of the estimate.